PENGARUH KOMPETENSI APARATUR DESA DAN SISTEM PENGENDALIAN INTERNAL TERHADAP NIAT UNTUK MELAKUKAN FRAUD DALAM PENGELOLAAN DANA DESA - Sabirin, sabirin (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2025)
The purpose of this study was to determine and analyze the influence of the village apparatus and internal control system on the intention to commit fraud. As well as to find out and analyze whether moral sensitivity moderates the competence of village officials and internal control systems against intentions to commit fraud in the management of village funds. This research is causal (causal research). The population of the study was all village finance officers in Sambas Regency, which were 193 people. Meanwhile, the sampling method is using simple random sampling with sample measurement using the Slovin formula. The selected sample is 130 respondents. From the selected sample, 112 respondents were eligible for data processing. The analysis technique used is analysis of multiple regression. The results showed that the competence of the village apparatus and the internal control system had a positive and significant effect on the intention to commit fraud, which means the better the competence of the village apparatus and the internal control system, the lower the intention to commit fraud. Keywords: Village Apparatus Competence, Internal Control System, Intention to Fraud